Relationship between running demands in friendly match and aerobic-anaerobic field test results in youth soccer players - Isikdemir, E.; Köklü, Y.; Alemdaroglu, B. U.; Asçi, A. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Field test performance is a key indicator of soccer match performance, offering insights into aerobic and anaerobic capacities. This study investigated the relationship between field test performance and match performance in young soccer players.